EFFORTS TO IMPROVE THE LEARNING RESULTS OF INDONESIAN LANGUAGE SPO WRITING MATERIALS THROUGH THE CONTEXTUAL TEACHING AND LEARNING MODEL IN GRADE II STUDENTS OF SD NEGERI MUARA KATI LAMA - Anadia Kaporina (Teaching and General Education Studies, 2025)
This research aims to determine the completeness of Indonesian language learning outcomes. Increasing Indonesian Language Learning Outcomes for SPO Writing Material through the Contextual Taeching and Learning Model in Class II Students at SD N Muara Kati Lama. The type of research is Classroom Action Research (PTK) with 14 class II students as subjects, consisting of 7 boys and 7 girls. Data was collected through tests, observation and documentation, and analyzed descriptively qualitatively and descriptively quantitatively. This research consists of three cycles with planning, implementation, observation and reflection stages. The results show that Indonesian language learning outcomes have increased. In conclusion, Indonesian Language Learning Outcomes: Efforts to Improve Indonesian Language Learning Outcomes for SPO Writing Material through the Contextual Taeching and Learning Model have increased and are an effective alternative for improving student learning outcomes.